Perception of conflict in students of the Francisco José Caldas School of Cúcuta from Galtung's theory (Praxis Educativa, 2024)
The research explored school coexistence from the students' perception of conflict, and was developed under a mixed descriptive approach. The conceptual foundation included information associated with the construction of reality, conflict and violence, as seen from Galtung's theory. The fieldwork was based on a non-probabilistic sampling, corresponding to 24 students of the Francisco José Caldas School of Cúcuta in Norte de Santander, Colombia. The diagnosis showed that perceptions of conflict correspond to the notion of direct violence, are based on negative implicit appraisals, and are difficult to modify. In addition, students have a low capacity to develop explicitly grounded conceptions, since the cultural and social environment repeatedly presents conflict in a negative way. The results can contribute to the formulation of strategies for the construction of a healthy school coexistence.
Keywords: social conflict; peaceful coexistence; peace; perception; violence